2018
DOI: 10.1177/1024258918761564
|View full text |Cite
|
Sign up to set email alerts
|

Self-employed professionals in the European labour market. A comparison between Italy, Germany and the UK

Abstract: The transition to an on-demand service economy, supported by unprecedented technological developments and the digital revolution, has modified traditional self-employed professions and generated new ones, fostering the growth of a body of highly qualified and hyper-specialised self-employed professionals in the European economies. An analysis of this phenomenon highlights three critical questions, connected to their position in the labour market: 1) the contested definition of their legal status and the (ad ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 9 publications
0
10
0
5
Order By: Relevance
“…In some cases, it is also possible to identify "dependent self-employed workers, " who do not have neither employees nor economic autonomy and control over their business (Eichhorst et al, 2013;Eurofound, 2017;Mondon-Navazo, 2017). However, beyond these classifications, statistics do not currently allow for consideration of the high heterogeneity of solo self-employment, where we can find genuine self-employment, but also a growing precariousness (including among workers who enjoy working as freelancers), as well as bogus or imposed false selfemployment (Schulze Buschoff and Schmidt, 2009;Westerveld, 2012;Leighton, 2015;Borghi et al, 2018;Conen and Schippers, 2019). Moreover, these conditions may occur to the same person, and possibly even simultaneously, especially to those people who perform different jobs at the same time.…”
Section: Trends and Heterogeneity Of Solo Self-employmentmentioning
confidence: 99%
“…In some cases, it is also possible to identify "dependent self-employed workers, " who do not have neither employees nor economic autonomy and control over their business (Eichhorst et al, 2013;Eurofound, 2017;Mondon-Navazo, 2017). However, beyond these classifications, statistics do not currently allow for consideration of the high heterogeneity of solo self-employment, where we can find genuine self-employment, but also a growing precariousness (including among workers who enjoy working as freelancers), as well as bogus or imposed false selfemployment (Schulze Buschoff and Schmidt, 2009;Westerveld, 2012;Leighton, 2015;Borghi et al, 2018;Conen and Schippers, 2019). Moreover, these conditions may occur to the same person, and possibly even simultaneously, especially to those people who perform different jobs at the same time.…”
Section: Trends and Heterogeneity Of Solo Self-employmentmentioning
confidence: 99%
“…As for those voluntarily in dependent self-employment, besides the recognition of a third hybrid category which has started to be adopted by some countries (e.g., Germany, Italy, Netherlands, Portugal), measures aiming to extend their limited rights can be pursued. As a comparative study on self-employed professionals in Italy, Germany and UK concluded, there is a need for a more universal social protection system to reduce the gap between those in selfemployment and those in dependent employment (Borghi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In Western economies, the transition to a service economy, supported by the use of information technologies and digital platforms, has modified traditional 2. This includes the growing instability of professional careers (Bologna, 2007;Ranci, 2012), limited inclusion in the welfare system compared to employees (Semenza et al, 2017;Borghi et al, 2018) and low income for a significant number of professional self-employed workers (Di Nunzio and Toscano, 2015). independent professions and created new ones.…”
Section: Independent Professionals In Europementioning
confidence: 99%
“…These changes have fostered the proliferation of highly qualified and specialized self-employed in many areas of the tertiary activity sector. The cross-country analysis of this phenomenon in Europe (Borghi et al, 2018) has highlighted three critical aspects: uncertain legal status, weak social protection and the large fragmentation of collective representation in environments of strong individualization of employment relationships. In the European research (I-WIRE, 2016), there are some signs of a better awareness of the challenges arising in these new labour markets.…”
Section: Independent Professionals In Europementioning
confidence: 99%